2020
DOI: 10.1038/s41598-020-76033-1
|View full text |Cite
|
Sign up to set email alerts
|

The POLD1R689W variant increases the sensitivity of colorectal cancer cells to ATR and CHK1 inhibitors

Abstract: Inhibition of the kinase ATR, a central regulator of the DNA damage response, eliminates subsets of cancer cells in certain tumors. As previously shown, this is at least partly attributable to synthetic lethal interactions between ATR and POLD1, the catalytic subunit of the polymerase δ. Various POLD1 variants have been found in colorectal cancer, but their significance as therapeutic targets for ATR pathway inhibition remains unknown. Using CRISPR/Cas9 in the colorectal cancer cell line DLD-1, which harbors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…The CRISPR/Cas9 technique offers a new approach to potentially edit any desired genome region. Nevertheless, the engineering of POLE and POLD1 in mammalian cells has been scarce and mainly performed in MMRd cell lines ( Hodel et al, 2020 ; Job et al, 2020 ). In our case, the CRISPR-driven POLD1 editing was a major challenge in the MMR-proficient SW837 cell line and could not be accomplished for POLD1 p.(Lys648fs*46).…”
Section: Discussionmentioning
confidence: 99%
“…The CRISPR/Cas9 technique offers a new approach to potentially edit any desired genome region. Nevertheless, the engineering of POLE and POLD1 in mammalian cells has been scarce and mainly performed in MMRd cell lines ( Hodel et al, 2020 ; Job et al, 2020 ). In our case, the CRISPR-driven POLD1 editing was a major challenge in the MMR-proficient SW837 cell line and could not be accomplished for POLD1 p.(Lys648fs*46).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between two genes, in which single mutations alone are compatible with cell survival, but mutation of both leads to death, is defined as synthetic lethality [ 31 ]. Based on this concept, multiple studies demonstrated that colorectal cancer with deficient POLD1 activity possessed the increased sensitivity to ATR and CHK1 inhibitors in preclinical models [ 32 , 33 ]. However, the effect and underlying mechanisms of POLD1 in HCC are not well-understood.…”
Section: Discussionmentioning
confidence: 99%
“…We start our analysis by aggregating a list of known and agreed driver variants in the POLE/D1 genes, based on information in ClinVar 12 , as well as literature review 4,9,[15][16][17][18][19][20] (Table S2, Methods). We then classified tumors as PPD based on having a high number of SNVs and high activity of PPD related signatures.…”
Section: Classifying Samples With Ppdmentioning
confidence: 99%